Prenatal Study of Iraqi Sheep Fetuses Skulls (Ovis aries) Through Using Different Techniques: Morphological Study (NTU Journal of Agriculture and Veterinary Science, 2025)
This work aims to prepare the skulls of Iraqi sheep fetuses during restricted periods of embryonic development for prenatal morphological study using different techniques.The skull consists of two parts: the calvarium, which contains the brain, that also called the neurocranium, and the facial part of the skull, that also called the visceral cranium. Thirty five samples of local Iraqi sheep fetuses were taken over regular visits to the slaughterhouses, aged between 72 to 155 days of pregnancy. Maceration, radiography, and fly larvae were the different methods to prepare the fetuses’ skull bones for prenatal morphological study. The method of maceration with sodium hydroxide solution (NaOH) and radiography of embryos heads’ showed that the frontal, parietal, inter-parietal, and squamous part of the temporal bone appeared fully ossified at the end of  the second trimester of pregnancy, while the occipital, sphenoid, the vertical plate of the ethmoid bone, and the petrous part of the temporal bone appeared fully ossified in the third trimester of pregnancy. While the fly larvae maceration method showed that the bones seemed fully ossified at the end of  the second trimester and in the third trimester of pregnancy, but were separated from each other.In conclusion, the best methods for the prenatal study of fetuses’ skulls are the maceration by NaOH and the radiography which allows us to achieve the anatomical measurements of fetuses’ skulls. In contrast, the maceration by fly larvae allows us to study the surface area of each bone.